## Simplify Math Problems Solution1

In this page simplify math problems solution1 we are going to see solution of practice questions of the worksheet simplify math problems.

(1) Simplify the following rational expression into their lowest forms

(i)   (6 x² + 9 x)/(3 x² - 12 x)

Solution:

= (6 x² + 9 x)/(3 x² - 12 x)

We are going to bring 3x from the numerator and denominator

= [ 3 x (2 x + 3) ]/[ 3 x (x - 4) ]

= (2 x + 3)/(x - 4)

(ii)   (x² + 1)/(x⁴ - 1)

Solution:

= (x² + 1)/(x⁴ - 1)

= (x² + 1)/(x²)² - (1²)²

= (x² + 1)/[(x² + 1²)(x² - 1²)]

Now we are going to use the following algebraic formula to simplify this rational expression.

a² - b² = (a + b ) (a -b)

= (x² + 1)/[(x² + 1²)(x + 1)(x - 1)]

= 1/(x + 1)(x - 1)

= 1/(x² - 1)

(iii)  (x³ - 1)/(x² + x + 1)

Solution:

= (x³ - 1)/(x² + x + 1)

Now we are going to use the following algebraic formula

a³ - b³ = (a -b) (a² + ab + b²)

= (x - 1)(x² + x + 1)/(x² + x + 1)

= (x - 1)

(iv)  (x³ - 27)/(x² - 9)

Solution:

= (x³ - 27)/(x² - 9)

= (x³ - 3³)/(x² - 3²)

Now we are going to use the following algebraic formula

a³ - b³ = (a -b) (a² + ab + b²)

a² - b² = (a + b ) (a -b)

= [ (x - 3)(x² + 3x + 9) ]/[ (x + 3) (x -3) ]

= (x² + 3x + 9)/(x + 3)

(v)  (x⁴ + x² + 1)/(x² + x + 1)

Solution:

= (x⁴ + x² + 1)/(x² + x + 1)

Now we are going to use the following algebraic formula

(x⁴ + x² + 1) = (x² + 1)² - x²

= [ (x² + 1)² - x² ]/(x² + x + 1)

= [ (x² + 1 + x) (x² + 1 - x) ]/(x² + x + 1)

= [ (x² + x + 1 ) (x² - x + 1) ]/(x² + x + 1)

=  (x² - x + 1)

simplify math problems solution1 simplify math problems solution1

Featured Categories

Math Word Problems

SAT Math Worksheet

P-SAT Preparation

Math Calculators

Quantitative Aptitude

Transformations

Algebraic Identities

Trig. Identities

SOHCAHTOA

Multiplication Tricks

PEMDAS Rule

Types of Angles

Aptitude Test